Design and fabrication of automatic can crusher / Muqri Azfar Mohd Faizar - Mohd Faizar, Muqri Azfar (2023)
A mechanical can crusher has been used for a very long time. Since, that many design and fabrication can crusher have been invented. The design of the can crusher will be operated automatically. This project mainly about generating a new concept of a can crusher that can crush two cans simultaneously. To put one can after one can that had been crushed in the machine it can be dangerous for the hands and the timing has to be perfect. Therefore, the users can face injury and take times of compression. Arrangement of the cans will be horizontally when placed in the slider and take turn to be compressed. The cans will be crushed automatically by a pneumatic piston when users push the button. Once the cans are compressed, they will fall into the box. This machine will reduce time of compression. Besides, it is inexpensive than the market price.